Cell-Based Tissue Engineering for Guided Bone Regeneration in Rats: A Preliminary Study with 3D-Printed β-Tricalcium Phosphate Scaffolds and Polydioxanone Membranes - Pitol-Palin, Letícia [UNESP]; Moura, Juliana [UNESP]; Frigério, Paula [UNESP]; Batista, Fábio Roberto de Souza [UNESP]; Saska, Sybele; Oliveira, Letícia; Matsubara, Elaine; Pilatti, Livia; Câmara, Diana; Lizier, Nelson; Blay, Alberto; Shibli, Jamil; et al. (Springer Nature, 2024)
Treatment of complex craniofacial deformities is still a challenge for medicine and dentistry because few approach therapies are available on the market that allows rehabilitation using 3D-printed medical devices. Thus, this preliminary study aims to evaluate the bioactivity of 3D-printed β-tricalcium phosphate (β-TCP) scaffolds and polydioxanone membrane (PDO) with cell-based (ASCs) tissue engineering for guided bone regeneration in critical calvary defects of rats. Methods: Male rats were divided into three groups: β-TCP + PDO membrane (TCP/PG), β-TCP/ASCs + PDO membrane (TCPasc/PG), and β-TCP/ASCs + PDO membrane/ASCs (TCPasc/PGasc). A surgical defect in the right parietal bone was made, and the defect was filled with the 3D-printed β-TCP scaffold and PDO membrane with or without ASCs. The animals were euthanized 7, 14, and 30 days after the surgical procedure for histomorphometric and immunolabeling analyses. Results: Cell-based therapy promotes, especially in the TCPasc/PGasc group, a bone area formation at the defect border region and the center of the defect. Conclusions: Using 3D-printed β-TCP scaffolds and PDO membranes associated with cell-based therapy has excellent potential to improve and accelerate guided bone regeneration. Moreover, using ASCs optimized the bioceramics by increasing its osteoinductive and osteoprogenitor capacity even with the resorption of the printed scaffold.